Extracting fish abundance indices from recreational fishing competition data - Dickens, John (Percy FitzPatrick Institute of African Ornithology, 2016)
Over-exploited fisheries result in global economic losses and can lead to the degradation of marine ecosystems. Commercial and recreational fisheries have grown substantially over the past decades placing fish stocks under increasing pressure. Fisheries management aims to conserve and restore stocks to economically and environmentally sustainable levels. Stock assessments are mostly based on analyses of fishery-dependent data, however, this practice often neglects uneconomically important species, making ecosystem approaches to fisheries management challenging. Competitive recreational angling has the potential to provide accurate and consistent records of catch and effort data for a variety of unassessed fish species as well as data for currently assessed commercial species, but without the market influence on targeting. The data from five boat based recreational competitions in the Western Cape were studied. Records for the competitions varied in length with the longest dataset from running from 1994 to 2014, and the shortest from 2003 to 2014. The competitions were divided into three inshore and two offshore groups with each targeting different assemblages of fish. In total 38 species of teleost were caught, but at least 90% of the total catch for each competition was comprised of seven species or less. Catch composition was determined for each competition and the standardised catch per unit effort (CPUE) of the ten most abundant species across the competitions were assessed. CPUE trends for red roman, snoek and geelbek were comparable to commercial fishery-dependent CPUE data. The targeting of specific species in the multi-species fishery noticeably influenced CPUE values. Catch limits resulted in lower estimations of the CPUE for snoek, and potentially for red stump nose. Boat based competition data is accurate and consistent enough for the extraction of abundance indices for certain species. Further work on these data may involve the standardisation of CPUE values to account for targeting in the multi-species fishery. With a large number of boat based competitive anglers in the country, there is a scope for using these data for stock assessments, either as stand-alone data sources, or as an adjunct to well-established commercial catch time-series.